THE INFLUENCE OF THE DARE TO BE BARE CAMPAIGN ON BRAND IMAGE ON INSTAGRAM @RAIKUBEAUTY - Octaviana, Vanisha; Susilo, Daniel; Vidal, Mateo Jose A. (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
A woman's beauty comes from within, not from the outside. Raiku Beauty is able to establish itself amid its long-established beauty product competitors, despite its youth. Through @RaikuBeauty, Raiku Beauty uses Instagram to transmit messages and communicate a product in order to establish a brand image. The goal of this research was to determine whether there is an effect of @Raikubeauty Instagram social media content on the dare to be bare campaign on the Image Raiku brand. Quantitative explanatory research is used, including data collection techniques in the form of surveys. The population consisted of @Raikubeauty followers, with a sample size of 395 responses calculated using the Taro Yamane formula, and the hypothesis was tested using simple linear regression. The findings of hypothesis testing suggest that social media content on Instagram regarding the campaign dare to be bare has a substantial effect on brand image by 60.2 percent. This suggests that the dimensions of campaign-related social media material have an impact on brand image.